2015
DOI: 10.1021/acs.jmedchem.5b01390
|View full text |Cite
|
Sign up to set email alerts
|

Important Hydrogen Bond Networks in Indoleamine 2,3-Dioxygenase 1 (IDO1) Inhibitor Design Revealed by Crystal Structures of Imidazoleisoindole Derivatives with IDO1

Abstract: Indoleamine 2,3-dioxygenase 1 (IDO1), promoting immune escape of tumors, is a therapeutic target for the cancer immunotherapy. A number of IDO1 inhibitors have been identified, but only limited structural biology studies of IDO1 inhibitors are available to provide insights on the binding mechanism of IDO1. In this study, we present the structure of IDO1 in complex with 24, a NLG919 analogue with potent activity. The complex structure revealed the imidazole nitrogen atom of 24 to coordinate with the heme iron, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(128 citation statements)
references
References 47 publications
4
124
0
Order By: Relevance
“…Those included 10 structures with the following pdb codes: 2D0T, 2D0U, 4PK5, 4PK6; 4U72, 4U74, 5EK2, 5EK3, 5EK4, 5ETW 16, 17, 18. The POPS program was used to calculate solvent‐accessible surface area (SASA) of residues and the fraction of SASA relative to total surface area of a residue (Q SASA ) 19.…”
Section: Methodsmentioning
confidence: 99%
“…Those included 10 structures with the following pdb codes: 2D0T, 2D0U, 4PK5, 4PK6; 4U72, 4U74, 5EK2, 5EK3, 5EK4, 5ETW 16, 17, 18. The POPS program was used to calculate solvent‐accessible surface area (SASA) of residues and the fraction of SASA relative to total surface area of a residue (Q SASA ) 19.…”
Section: Methodsmentioning
confidence: 99%
“…After deleting chain B, the Protein Preparation Wizard (Maestro 10.6, Schrödinger, Inc., NY, USA) tool was used to prepare chain A adding hydrogen atoms, setting ionization states at pH 7.0 and refining the structure by energy minimization. The oxidation state of the iron atom of the heme group was set to Fe 3+ [31,[43][44]. A grid box was generated with Glide 7.1 (Schrödinger, Inc., NY, USA), locating the center on the center of mass of the cocrystallized ligand (S, R)-11 in 5EK3.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Germane to this aspect, many IDO1 inhibitors reported in the literature have been described as endowed with noncompetitive or uncompetitive inhibition kinetics with respect to L-Trp (1) [3,30]. Crystallographic studies have shown that at least some of these compounds bind to the catalytic cleft of the enzyme [31][32][33]. Accordingly, their 'apparent' noncompetitive or uncompetitive profile is due to competition with binding of oxygen to heme, and not to the interaction with an accessory-binding site of the protein.…”
mentioning
confidence: 99%
“…Since removal of the two carbonyl groups has a detrimental effect on the inhibition potency of the chlorinated derivatives (see 5,6, and 16), we retained the C2 carbonyl group and explored the effect of substitutions at the C3 position alone. As before, the effect of C3 substitutions was assessed in the presence and absence of chlorines.…”
Section: Substitutions At C3mentioning
confidence: 99%
“…Due to the early identification of IDO1 as an enzyme with immunomodulatory function and its broad expression in the body, it became the main target for drug discovery. Many years of research have revealed a large number of IDO1 inhibitors with affinities that reach the low nanomolar region 1,[5][6][7][8] . Of these, the most promising candidate, known as INCB024360, is currently under investigation in clinical trials 9 .…”
Section: Introductionmentioning
confidence: 99%